UJI DAYA TERIMA SELAI KULIT JERUK MANIS (Citrus sinensis L) DAN NILAI GIZINYA - Renita Debora Simanjuntak; Etti Sudaryati; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
The waste of sweet orange peel getting from juice of the sweet orange can be added as one of the food stuff diversification which is easy to made and become interesting for public consumption, namely jam. Jam is semi-solid food stuff that have sweet taste and make public love it. Furthermore jam also can be consumed by people in all age groups. The aim of this research is to know the acceptance of public and nutrient contained from the sweet orange peel jam. This research was experiment that  involved 30 panelists from Public Health Study University of North Sumatera Utara Medan. Date of acceptance experiment is processed manually and analyzed by using descriptive analysis percentage. Nutrient analysis was tested in Laboratory of Industrial Research and Standardization Agency Medan (Laboratorium Balai Riset Dan Standardisasi Industri Medan) and Laboratory of Biochemistry/ KBM FMIPA USU Medan. The result of this experiment showed that based on organoleptic test on taste, scent, color and texture, panelists like the sweet orange peel jam with percentage of taste 90.0%, scent 79.9%, color 98.8%, and texture 94.4%. Based on laboratory test, the content of water 67.25%, content of ash 0.78%, content of protein 0.56%, content of calcium 0.67%, content of fat 0.35%, content of carbohydrate 31.06 % and content of vitamin C 29.60%. It is recommended for people to be able to utilize the sweet orange peel become kind of jam as an additional stuff and topical ingredient in bread. Keywords: Acceptance test, jam, sweet orange peel, nutrient content